Therapy Modalities, Prognostic Factors, and Outcome of the Primary Cervical Carcinosarcoma: Meta-analysis of Extremely Rare Tumor of Cervix. Issue 9 (1st November 2017) - Kimyon Comert, Gunsu; Turkmen, Osman; Karalok, Alper; Basaran, Derman; Bulbul, Dilek; Turan, Taner
Abstract : Objective: The aim of this study was to evaluate the prognostic factors, treatment options, and survival outcomes of primary carcinosarcomas of the uterine cervix. Methods: An electronic search of the literature was conducted from 1951 to February 2017 to identify articles on primary cervical carcinosarcoma. After comprehensive evaluation of case series and case reports, 81 cases were included in the study. Results: The most common clinical FIGO (International Federation of Gynecology and Obstetrics) stage was IB at 53% of cases. Median follow-up time was 15 months (range, 1.75–156 months). Two-year disease-free survival (DFS) and overall survival (OS) of the entire cohort were 49% and 60%, respectively. Both 2-year DFS and OS were significantly higher in patients with stage I than in those with stage II disease or greater (73% vs 22%, P = 0.000 and 82% vs 33%, P = 0.000, respectively). Two-year OS was 17% for patients who received primary radiotherapy, whereas it was 68% for those who underwent only surgery ( P = 0.003). Surgery followed by adjuvant radiotherapy with or without chemotherapy was significantly associated with improved DFS and OS compared with primary radiotherapy. Two-year DFS was 63% in patients who underwent primary surgery, whereas it was 100% in patients treated with primary surgery followed by adjuvant radiotherapy with chemotherapy ( P = 0.030). Stage alone was an independent prognostic factor for risk of both recurrence and death (hazard ratios, 9.8 [ P = 0.004] and 14 [ P = 0.018], respectively). Conclusions: In due course of presentation, the tumor stage has a great importance because it is the only independent factor for prognosis. Surgery followed by adjuvant radiotherapy with or without chemotherapy seems to be related with better OS and DFS.